Private Natural Forests Management in Madhya Pradesh - Dixit, M. (Indian Forester, 2007)
Madhya Pradesh has about 1,000 km2 of Private Natural Forests belonging to roughly 20,000 agriculturists in almost all the districts, the tribal share being 15%. The natural forests occur on the uncultivable portions of ’Bhumiswami’ land and comprise of valuable teak over major areas. The M.P. Lok Vaniki Act, 2001 laid the foundation of the Small-Scale Private Forest Management in the country for the first time in Madhya Pradesh. Private forests, a great natural resource, offer vast opportunities for developing State’s Rural Economy besides their environmental role as seen from the implementation of management plans in Dewas District of Madhya Pradesh. Private forests management is the only hope of achieving 33% of forest cover in the State in accordance with the National Forest Policy. The Ministry of Environment and Forests, Government of India is required to deal with this very valuable aspect of forestry in the country with assured success without any financial implications.